Impacto de drogas antiplaquetárias na doença e no reparo periodontal experimental em ratos - Coimbra, Leila Santana [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Platelets are a natural reservoir of several biological mediators and once activated, express growth factors, pro- and anti-angiogenic factors, chemokines and monoamines modulating the activation and maintenance of the inflammatory and repair process. The aim of this study was to evaluate the impact of antiplatelet drugs, aspirin (Asp) and clopidogrel (Clop) on periodontal disease and the repair of periodontal tissues after induction of experimental periodontitis in rats. For the evaluation of the inflammatory process, microscopic evaluation, analysis of the expression of the chemokines CXCL4 and CCL5 by ELISA and myeloperoxidase activity (MPO) were realized. To evaluate periodontal tissue repair we performed microscopic examination, analysis of the expression of CXCL12, CXCL4, CCL5 and PDGF by ELISA, and blood vessels and osteoclast count by immunohistochemistry. Also, characterization of undifferentiated mesenchymal stem cells by immunohistochemical staining for CD 271 (stem cell marker) and immunofluorescence double labeling using CD 271 associated with CD45, Ki67 and TUNEL were realized. Undifferentiated mesenchymal stem cells derived from human bone marrow were used for in vitro evaluation of cell proliferation by immunocitofluorescence. Three days after ligature placement, we found that treatment with antiplatelet drugs abbreviated the inflammatory process observed by the microscopic analysis, reduction of myeloperoxidase activity (p <0.001) and decreased the expression of CXCL4 (p <0.05), but treatment with Clop more pronounced than Asp. After removal of the ligature, Clop treatment accelerated the repair process by significantly reducing the expression of CXCL12, CXCL4, PDGF number of blood vessels and osteoclasts, on the other hand, treatment with Asp only showed significant effects in reducing the expression of CXCL12 and CXCL4. In turn, Clop treatment increased the number of osteoblasts...

As plaquetas são um reservatório natural de diversos mediadores biológicos e, uma vez ativadas, expressam fatores de crescimento pró e anti-angiogênicos, quimiocinas e monoaminas, modulando a ativação e manutenção dos processos inflamatório e de reparo. Os objetivos deste trabalho foram avaliar o impacto do tratamento com drogas antiplaquetárias, aspirina (Asp) e clopidogrel (Clop), sobre a doença periodontal e o processo de reparação dos tecidos periodontais após indução de periodontite experimental em ratos. Para a avaliação do processo inflamatório foram realizadas análise microscópica, análise da expressão das quimiocinas CXCL4 e CCL5 por ELISA e da atividade de mieloperoxidase (MPO). Para avaliação do reparo dos tecidos periodontais, foram realizadas análise microscópica, análise da expressão de CXCL12, CXCL4, CCL5 e PDGF por ELISA, contagem de osteoclastos e vasos sanguíneos através de reações de imunohistoquímica e caracterização das células mesenquimais indiferenciadas por imunohistoquímica para CD 271 e imunofluorescência de dupla marcação utilizando CD 271 associado ao CD45, KI67 e TUNEL. Células mesenquimais indiferenciadas derivadas da medula óssea de humanos foram utilizadas in vitro para avaliação da proliferação celular por imunocitofluorescência. Três dias após a instalação da ligadura, verificou-se que o tratamento com as drogas antiplaquetárias abreviou o processo inflamatório, observado através dos aspectos microscópicos, da redução da atividade da enzima mieloperoxidase (p<0.001), e queda da expressão de CXCL4 (p<0.05), entretanto o tratamento com Clop de forma mais acentuada que o da Asp. Após retirada da ligadura, o tratamento com Clop acelerou o processo de reparo através da redução significativa da expressão de CXCL12, CXCL4, PDGF, número de vasos sanguíneos e osteoclastos; por outro lado, o tratamento com Asp...
Keywords: Periodonto; Plaquetas (Sangue); Aspirina; Doenças periodontais; Periodontium